Soshanguve Paremiology+: A Multilingual Approach - Napjadi Letsoalo; Mpho Ngoepe; Puleng LenkaBula; Juliet C. Kamwendo; Munyaradzi Mushonga; Delvah Mabaso; Moffat Sebola; Sikheto J. Kubayi; Bulelwa Nokele; Maropeng Maponya; Kganathi Shaku (AOSIS, 2025)
This scholarly book explores the transformative role of proverbs in cultural education, preservation and scholarly discourse in South Africa. It emphasises the importance of integrating indigenous African knowledge into academic spaces to support decolonisation, (re)Africanisation and transformation. Proverbs are presented as tools for promoting multilingualism, multiculturalism, social cohesion and mutual respect in South Africa's diverse society. The book addresses the United Nations'(UN) Sustainable Development Goal (SDG) 4 (quality education), SDG 5 (gender equity), SDG 9 (innovation) and SDG 10 (reduce inequality). It serves as a teaching resource for proverbs in Northern Sotho/Sepedi, Sesotho, Setswana, Xitsonga, isiZulu, isiXhosa, isiNdebele, siSwati and/or Tshivenḓa (Sotho, Shangaan, Nguni and Venḓa, i.e. Soshanguve), as well as Chichewa and Shona, supporting cross-cultural understanding. Grounded in a scholarly project on a multilingual proverbs dictionary, the book applies theoretical frameworks such as conceptual metaphor theory, ethnopragmatics and translation quality assessment to analyse proverbs. This interdisciplinary approach bridges linguistics, anthropology and digital humanities, offering fresh insights into the semantics and cultural significance of proverbs. The chapters in the book explore themes like proverbs in music, their intersection with patriarchy, and translation quality assessment. Targeted at scholars and experts in languages, literature, linguistics and digital humanities, the book advances the study of proverbs while fostering cultural awareness and sensitivity. It highlights the value of proverbs as linguistic and cultural assets, enriching academic and practical applications across disciplines.